Hadith #2275 - Sahih Muslim - Amr bin Dinar عمرو بن دينار الأثرم الجمحي (Sahih Muslim)
I went to his house in San’a’ and he offered me nuts grown in his house to eat. And his brother said: I heard Mu’awiya b. Abu Sufyan saying that he had heard the Messenger of Allah (ﷺ) as saying, and then he made a mention (of a hadith) like one mentioned above.
Grade: Sahih

Hadith #2881 - Sahih Muslim - Amr bin Dinar عمرو بن دينار الأثرم الجمحي (Sahih Muslim)
We asked Ibn Umar about a person who came for Umra and circumambulated the House, but he did not run between al-Safa’ and al-Marwa, whether he is allowed to (put off Ihram) and have intercourse with his wife. He replied: Allah’s Messenger (ﷺ) circumambulated the House seven times and offered two rak’ahs of prayer after staying (at ‘Arafat), and ran between al-Safa and al-Marwa seven times.” Verily there is in Allah’s Messenger a model pattern for you” (xxxill. 21).
Grade: Sahih

Hadith #3807 - Sahih Muslim - Amr bin Dinar عمرو بن دينار الأثرم الجمحي (Sahih Muslim)
” We abandoned it (renting) on account of that.”
Grade: Sahih